2018
DOI: 10.1002/adv.21942
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of highly effective flame‐retardant unsaturated polyester resin system based on multiple strategies

Abstract: Considered that unsaturated polyester resin (UPR) as one of the most commonly used thermoset materials often exhibit severe fire hazards, graphene can be used to act as barriers to enhance the flame retardancy of UPR. However, graphene easily shows irreversible aggregation when being introduced into polymer matrix, which limits its further application in industry. In this work, we synthesized a novel organophosphorus oligomer (DHP), which contained double bond and multivalent phosphorus (−1 and +5) with highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The C1s binding energy of (Pt/BTA)‐0 and (Pt/BTA)‐3 was as shown in Figure 10C,D, 284, 284.8, 286.1, and 289 eV corresponding to CSi, CC, CO, and CO, respectively 27,28 . Peaks of C1s at 284 eV (CSi) and 284.8 (CC) became stronger after adding Pt/BTA, while peaks at 286.1 eV (CO) and 289 eV (CO) became weaker.…”
Section: Resultsmentioning
confidence: 90%
“…The C1s binding energy of (Pt/BTA)‐0 and (Pt/BTA)‐3 was as shown in Figure 10C,D, 284, 284.8, 286.1, and 289 eV corresponding to CSi, CC, CO, and CO, respectively 27,28 . Peaks of C1s at 284 eV (CSi) and 284.8 (CC) became stronger after adding Pt/BTA, while peaks at 286.1 eV (CO) and 289 eV (CO) became weaker.…”
Section: Resultsmentioning
confidence: 90%
“…Bautista et al reported a highly fire-retardant UP that achieved an LOI of 51% by combining 5 wt% of caged silsesquioxane oligomers and 55 wt% of ATH because of the high thermal stability of the compound containing Si-O type bonds in the structure [120]. Jiang et al [118] used an organophosphorus oligomer to functionalize GO (Fig. 11b), and only 2 wt% of functionalized GO reduced the PHHR of UP by 42%.…”
Section: Organic-inorganic Frsmentioning
confidence: 99%
“…In addition, Gr has been used to enhance the fire retardancy of thermoset materials such as UPR. Jiang et al [137] first synthesized a novel organophosphorus oligomer (DHP) and then prepared the G-DHP composite material. e introduction of 2.0 wt.% G-DHP significantly enhanced the fire retardancy of the UPR matrix, which was demonstrated by a 41.79% decrease in the peak exothermic rate (PHRR).…”
Section: Applications Of Graphene/polymer Composite Materialsmentioning
confidence: 99%